Analisis Pengaruh Indikator Makroekonomi Terhadap Profitabilitas Bank Himbara - Perdana, Arifin Widi; Purnamasari, Pupung; Aminah, Siti (LP2M IBK Nitro, 2025)
This research was conducted to determine the influence of macroeconomic variables consisting of Inflation, Interest Rates, Economic Growth and Exchange Rates on Profitability which is proxied by the Return On Assets (ROA) value on the research object, namely the member banks of Himbara Bank (State Bank Association). The research method used is a quantitative method, the type of data used is panel data sourced from macroeconomic indicators for 2015 - 2023. Data processing uses SPSS 27 software, the tests carried out are classical assumption tests and hypothesis tests. The research results show that partially inflation has no effect on ROA, interest rates have no effect on ROA, economic growth has no effect on ROA and exchange rates have no effect on ROA. The results obtained indicate that macroeconomic variables do not have a significant effect on the profitability of the research object because they only have an influence of 12.5%.